A Markowitz Approach For Asset Allocation In The Albanian Bond Market - Bezo, Ardi; Shehu, Hidajet; Manaj, Zamir (European Scientific Journal, ESJ, 2016)
Having reviewed all the components that meet a country’s financial system, the Albanian financial market landscape is asymmetrical. To date investments in Albania are realized mainly through bank deposits or securities in informal way or Bonds investments. However, a high proportion of the total assets of life insurance companies are invested in deposits of commercial banks, it is necessary to diversify the sources of investments and a weakening dependence on commercial banks. This restructuring will bring changes in investment policy and in the risk management philosophy. The analytical approach consists in how to diversificate the risk throwing Optimization portfolio of all markets actors, detailed analysis of all the limitations that offers the Albanian financial market, identifying financial instruments comprising the investment portfolio of financial institutions and building a model optimization which will bring increased value of investments. At the end of the paper will be conducted a comparative analysis in Albania Financial markets.